Recognising Effective Legal Protection to People Smuggled at Sea, by Reviewing the EU Legal Framework on Human Trafficking and Solidarity between Member States - Ventrella, Matilde (2015)
The death toll of migrants at sea is on the increase. The EU and its Member States are not addressing the situation by widening the EU legal framework on human trafficking to persons smuggled at sea. People smuggled at sea are extremely vulnerable at the hands of their smugglers and suffer serious abuse of their human rights from their journeys through the desert, on the boats and when they reach their final destination. They become victims of human trafficking and they should not be neglected anymore by the EU and its Member States. However, all EU proposals lack of concreteness as Member States do not want to support and host migrants at sea on their territories. They are reluctant to launch solidarity between each other as requested by the Lisbon Treaty and by doing this, they are indirectly responsible for the death of many migrants at sea and for the abuse of their human rights. This article proposes alternatives to explore that could change the situation if Member States show their willingness to cooperate with each other.